Adaptasi Sosial Warga Kedungharjo Golongan NU di Tempat Relokasi Warga Muhammadiyah Sebagai Dampak Pembangunan Proyek Jalan Tol Solo-Ngawi - Atika Yulianti; Iwan Nurhadi; Lutfi Amiruddin (Sociology Department, Brawijaya University, 2019)
This study discusses the social adaptation of the NU Kedungharjo (Nahdlatul Ulama) community in the relocation place of the Muhammadiyah community as a result of the construction of the Solo-Ngawi toll road. As a result of the development, residents of Kedungharjo who were affected by land acquisition had to move. In this study the Kedungahrjo community had moved in Sengon and Dukuhan Hamlets. The hamlet is an urban or semi-urban peri region with heterogeneous citizens in social, cultural areas including the existence of differences in Islamic religious groups between NU and Muhammadiyah. To overcome this, the residents of Kedungharjo must readjust to the place of movement in overcoming the differences in the Islamic religious group. The researcher chose to use the theory of Robert K. Merton to see the adaptation process that had been carried out by residents of Kedungharjo to overcome the differences in the religious groups by using 5 typologies from Merton namely Conformity, Ritualism, Retreatism, Innovation and Rebelion. The research method used is to use qualitative methods with the approach of case studies and data collection techniques through observation, interviews and documentation.The results of this study have found that residents of Kedungharjo adapted to overcome the differences in the religious group with a typology of conformity, namely following religious activities in the relocation site. The second typology is using ritualism, namely the people of Kedungharjo who still maintain the values and norms believed by the NU people. The third typology is to use the retreatism adaptation process, which is the form of resignation by not participating in the religious activities of the Muhammadiyah group. And the last typology in the process of adaptation carried out by residents of Kedungharjo is to use Innovation, namely by holding religious activities in the place of transfer. With adjustments made by the Kedungharjo community, they have experienced social articulation by not being able to mix it from the NU and Muhammadiyah groups from religious activities.Keywords: Urban Elf, NU and Muhammadiyah, Social Adaptation, Social Disarticulation.